Structural basis for C4 photosynthesis without Kranz anatomy in leaves of the submerged freshwater plant Ottelia alismoides. (16th January 2020) - Han, Shijuan; Maberly, Stephen C; Gontero, Brigitte; Xing, Zhenfei; Li, Wei; Jiang, Hongsheng; Huang, Wenmin
Abstract: Background and Aims: Ottelia alismoides (Hydrocharitaceae) is a freshwater macrophyte that, unusually, possesses three different CO2 -concentrating mechanisms. Here we describe its leaf anatomy and chloroplast ultrastructure, how these are altered by CO2 concentration and how they may underlie C4 photosynthesis. Methods: Light and transmission electron microscopy were used to study the anatomy of mature leaves of O. alismoides grown at high and low CO2 concentrations. Diel acid change and the activity of phosphoenolpyruvate carboxylase were measured to confirm that CAM activity and C4 photosynthesis were present. Key Results: When O. alismoides was grown at low CO2, the leaves performed both C4 and CAM photosynthesis whereas at high CO2 leaves used C4 photosynthesis. The leaf comprised an upper and lower layer of epidermal cells separated by a large air space occupying about 22 % of the leaf transverse-section area, and by mesophyll cells connecting the two epidermal layers. Kranz anatomy was absent. At low CO2, chloroplasts in the mesophyll cells were filled with starch even at the start of the photoperiod, while epidermal chloroplasts contained small starch grains. The number of chloroplasts in the epidermis was greater than in the mesophyll cells. At high CO2, the structure was unchanged but the thicknesses of the two epidermal layers, the air space, mesophyll and the transverse-section area of cells and air space were greater. Conclusions: Leaves of O. alismoides have epidermal and mesophyll cells that contain chloroplasts and large air spaces but lack Kranz anatomy. The high starch content of mesophyll cells suggests they may benefit from an internal source of CO2, for example via C4 metabolism, and are also sites of starch storage. The air spaces may help in the recycling of decarboxylated or respired CO2 . The structural similarity of leaves at low and high CO2 is consistent with the constitutive nature of bicarbonate and C4 photosynthesis. There is sufficient structural diversity within the leaf of O. alismoides to support dual-cell C4 photosynthesis even though Kranz anatomy is absent.